Theater for young people:theory and thematic on the society of XXI century - Morón, Antonio César (Didáctica. Lengua y Literatura, 2019)
Theatre for Young People is still a little treated gender and less studied by the researchers, as many times is included within the generic Children’s Theatre. A series of theoretical and thematic perspectives that help to define and understand the complex existence of a genre that on many occasions has been denied their same possibility of existence will be established from this article.